EFFECT OF DOMINANT FOLLICLE ABLATION ON OVARIAN FOLLICLE COUNT IN SAHIWAL CATTLE - P. Vamsi Krishna; L.S.S. Vara Prasad Reddy; B.R. Naik; M. Kalyana Chakravarthi; K. Veera Bramhaiah; A.V.N. Sivakumar; N. Venkata Krishna (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted to investigate the effect of dominant follicle ablation on follicle count in Sahiwal cattle. All the selected donor animals were randomly divided into two equal groups. Donor cows in group 1(n=10) were subjected to dominant follicle(s) ablation, donor cows in group 2(n=10) without ablation and both groups were administered with 10 µg GnRH followed by FSH in 3 divided doses @ 100 mg, 60 mg and 40 mg at 48, 60 and 72 hrs after GnRH administration. OPU was carried out 24 hrs after the last FSH administration in all the donor cows. The overall mean number of follicles available for aspiration by Ovum pick up (OPU) method were 7.43 ± 0.22 in group 1 and 6.19 ± 0.22 in group 2 and the difference in the number of follicles between groups was significant (p<0.05). Mean follicular count on right and left ovaries of group 1 cows were 7.87 ± 0.30 and 7.00 ± 0.30, respectively with a significant difference (p>0.05). whereas, mean follicular count on right and left ovaries of group 2 cows were 6.14 ± 0.32 and 6.24 ± 0.32, respectively without significant difference (p<0.05). While, the mean follicular count in group 1 at different timings of 0 hr, 48 hrs and 96 hrs were 7.15 ± 0.36, 7.60 ± 0.36 and 7.55 ± 0.36, respectively and in group 2 cows were 6.03 ± 0.39, 6.25 ±0.39 and 6.30 ± 0.39, respectively without significant (p>0.05). In conclusion, ablation of dominant follicle had higher follicular count in Sahiwal donor cows compared to non- ablation group cows.